1970
DOI: 10.3329/bjvm.v5i1.1321
|View full text |Cite
|
Sign up to set email alerts
|

Pathological investigation of liver of the slaughtered buffaloes in Barisal district

Abstract: Livers (n = 80) of slaughtered adult buffaloes were examined for pathological changes during the period from July 2006 to March 2007 in two slaughterhouses of Barisal district. Livers exhibiting gross alterations were cleaned with normal neutral saline and the changes were recorded. The lesions containing tissue samples were collected in 10% buffered formalin for fixation. Grossly, Gigantocotyle explanatum infection (amphistomiasis) was found in 31.25% and Fasciola gigantica infection was in 22.5% cases. Hydat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
(5 reference statements)
4
14
0
Order By: Relevance
“…Hydatid cysts have been commonly recorded in liver followed by lungs and majority of cysts are slow growing (Gemmell 1966). The results in the present study are in parity with many previous studies (Hussain et al 1992;Ahmedullah et al 2007). Barnes et al (2011) reported that adventitial layer in the multilocular cysts was thick in sheep which could be restrictive to growth while simultaneously protecting the hydatid from the host immune response.…”
Section: Discussionsupporting
confidence: 83%
“…Hydatid cysts have been commonly recorded in liver followed by lungs and majority of cysts are slow growing (Gemmell 1966). The results in the present study are in parity with many previous studies (Hussain et al 1992;Ahmedullah et al 2007). Barnes et al (2011) reported that adventitial layer in the multilocular cysts was thick in sheep which could be restrictive to growth while simultaneously protecting the hydatid from the host immune response.…”
Section: Discussionsupporting
confidence: 83%
“…The reason could be the availability of the snail intermediate host in this geographical region. The description of natural infection by E. explanatum is sporadic (Upadhayay et al 1987;Hafeez and Rao 1989;Wiedosari et al 1991;Ahmedullah et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of fascioliasis in slaughtered animals has been reported to be 15–66% in cattle [14, 28], 3.8–22% in goats [17, 29–31], 81% in sheep [32] and 23–47% in buffaloes [22, 33], respectively. The actual burden of fascioliasis - including subclinical disease - is likely much higher than that reported above [34].…”
Section: Introductionmentioning
confidence: 99%